Role of membrane contact sites in protein import into mitochondria - Horvath, Susanne E (Protein Sci, 2015)
Mitochondria import more than 1,000 different proteins from the cytosol. The proteins are synthesized as precursors on cytosolic ribosomes and are translocated by protein transport machineries of the mitochondrial membranes. Five main pathways for protein import into mitochondria have been identified. Most pathways use the translocase of the outer mitochondrial membrane (TOM) as the entry gate into mitochondria. Depending on specific signals contained in the precursors, the proteins are subsequently transferred to different intramitochondrial translocases. In this article, we discuss the connection between protein import and mitochondrial membrane architecture. Mitochondria possess two membranes. It is a long-standing question how contact sites between outer and inner membranes are formed and which role the contact sites play in the translocation of precursor proteins. A major translocation contact site is formed between the TOM complex and the presequence translocase of the inner membrane (TIM23 complex), promoting transfer of presequence-carrying preproteins to the mitochondrial inner membrane and matrix. Recent findings led to the identification of contact sites that involve the mitochondrial contact site and cristae organizing system (MICOS) of the inner membrane. MICOS plays a dual role. It is crucial for maintaining the inner membrane cristae architecture and forms contacts sites to the outer membrane that promote translocation of precursor proteins into the intermembrane space and outer membrane of mitochondria. The view is emerging that the mitochondrial protein translocases do not function as independent units, but are embedded in a network of interactions with machineries that control mitochondrial activity and architecture.